Clonal viability measurements on Plasmodium falciparum to assess in vitro schizonticidal activity of leupeptin, chloroquine, and 5-fluoroorotate. - Young, R D (1993)
Until now, the in vitro activity of potential antimalarial agents has been evaluated primarily by monitoring decreases in parasite proliferation. These traditional assays do not distinguish between compounds that arrest proliferation of parasites and compounds that kill them. In this report, a more complex in vitro cytocidal assay for Plasmodium falciparum is described. This assay measures the clonal viability of P. falciparum after the parasites have been treated with an antimalarial agent. The new assay was used to assess cytocidal activities of three antimalarial agents that work through unrelated mechanisms. Leupeptin, a protease inhibitor, arrested the proliferation of W2 clones of P. falciparum at a MIC of 50 microM, but at least 80% of leupeptin-treated cells were viable as judged by the cytocidal assay. On the other hand, chloroquine at 1 microM, its MIC for W2 cells, not only arrested parasite proliferation but also killed more than 99% of the cells. Earlier studies had shown that treatment of P. falciparum with 100 nM 5-fluoroorotate for 48 h was sufficient to inhibit parasite proliferation and parasite thymidylate synthase but not enough to cause significant incorporation of 5-fluoropyrimidines in parasite nucleic acids. By using the new schizonticidal assay, these conditions were found to be necessary and sufficient to kill all parasites in culture. Results of these studies are consistent with the hypothesis that 5-fluoroorotate-based inactivation of P. falciparum thymidylate synthase triggers a lethal mechanism against malarial parasites.